2018
DOI: 10.1002/chem.201802031
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Self‐Assembly Diversity in the Solid‐State by Chiral/Non‐Chiral ZnII‐Porphyrin Crystallization

Abstract: A chiral Zn porphyrin derivative 1 and its achiral analogue 2 were studied in the solid state. Considering the rich molecular recognition of designed metalloporphyrins 1 and 2 and their tendency to crystallize, they were recrystallized from two solvent mixtures (CH Cl /CH OH and CH Cl /hexane). As a result, four different crystalline arrangements (1 a,b and 2 a,b, from 0D to 2D) were obtained. Solid-state studies were performed on all the species to analyze the role played by chirality, solvent mixtures, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Various types of chiral porphyrins aside from steroidand sugar-modified porphyrins have been designed. [19][20][21][22][23][24][25] For instance, Meijer et al systemically studied the pathway complexity of the supramolecular polymerization of a chiral porphyrin. [26] A chiral amide-functionalized zinc porphyrin (S/R)-1 (Figure 1) was designed, and hydrogen bonding between the amide moiety and π-π stacking of the porphyrin skeleton was attributed to the formation of supramolecular polymers.…”
Section: Chiral Porphyrin Assemblies From the Molecules With Chiral P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of chiral porphyrins aside from steroidand sugar-modified porphyrins have been designed. [19][20][21][22][23][24][25] For instance, Meijer et al systemically studied the pathway complexity of the supramolecular polymerization of a chiral porphyrin. [26] A chiral amide-functionalized zinc porphyrin (S/R)-1 (Figure 1) was designed, and hydrogen bonding between the amide moiety and π-π stacking of the porphyrin skeleton was attributed to the formation of supramolecular polymers.…”
Section: Chiral Porphyrin Assemblies From the Molecules With Chiral P...mentioning
confidence: 99%
“…Various types of chiral porphyrins aside from steroid‐ and sugar‐modified porphyrins have been designed. [ 19–25 ] For instance, Meijer et al. systemically studied the pathway complexity of the supramolecular polymerization of a chiral porphyrin.…”
Section: Chiral Porphyrin Assemblies From the Molecules With Chiral P...mentioning
confidence: 99%
“…Moreover, we found that the presence of 100-fold molar excess of external nitrogen ligands, i.e., (R)- and (S)-1-phenylethylamine, dictated the stereochemical course of the self-assembly process, disregarding the stereochemistry of the L- or D-proline functionalities ( Figure 6 a) [ 73 ]. Furthermore, the species formed using an achiral ligand (i.e., benzylamine) no longer showed supramolecular chirality.…”
Section: Aggregation Behaviour and Supramolecular Chirogenesis Of The...mentioning
confidence: 99%
“…SEM images of ZnP(L)Pro(−) aggregates (10 μM; EtOH/H 2 O 25/75 v:v) in the presence of (R)-phenylethylamine (1 mM) ( b ) and without added nitrogen ligand ( c ). Adapted from OPEN ACCESS [ 73 ].…”
Section: Figures and Schemesmentioning
confidence: 99%
“…Related types of shapes are reported studying the effect of solvent and surfaces on some CP dispersions, showing that crystals are formed by domains that can disaggregate. 33 AFM topographic images, using the tapping mode for the SiO 2 /Si wafers, are shown in Fig. 8.…”
Section: Studies On the 2d Materials (Compound 2)mentioning
confidence: 99%